Avaliação da carga mental de trabalho dos operadores dos centros de operação e controle de energia elétrica. - Vitório, Daiana Martins (2012)
The concept of mental load of work is a product concept originated the concept of workload, generally understood as a field of interaction between the task requirements and the ability of human achievement. It follows from the fact, the worker perform the task itself. Currently there has been a significant increase of the changes imposed work situations in organizations especially with the introduction of information technology and process automation. Some factors associated with these changes need to be improved, there are still accidents and incidents in organizations, mainly induced by fatigue, lack of concentration or due to inadequate operator / screen / machine / computer. This study aims to evaluate the mental workload of the employees of the Centers of Technical Operation and Control of Electric Power. It identifies factors that contribute to the perception of their workload. For that we used a questionnaire with questions pertaining to demographic and functional aspects of members of the operators, questions about the workload and the method NASA-TLX. The survey was conducted in the centers for Disease Control and Operation of company of Electric Power in the states of Paraiba, Rio Grande do Norte and Pernambuco. The results indicated that the thermal environment and lighting are appropriate for work activities. The demands that contributed most to the overall rate of mental workload in terms of weight were followed by the Mental Required Time Requirement. The demand was less weight Frustration showing the engagement and commitment of the operators with the same work. It is intended that the results of this research can support improvements in management of the operation of companies in the electric sector, contributing to an improved quality of work.